2019
DOI: 10.1096/fj.201802373r
|View full text |Cite
|
Sign up to set email alerts
|

Direct repression of anoctamin 1 ( ANO1 ) gene transcription by Gli proteins

Abstract: The Ca2+‐activated Cl− channel, anoctamin 1 (Ano1, also known as transmembrane protein 16A) contributes to intestinal pacemaking, fluid secretion, cellular excitability, and tissue development. The human ANO1 promoter contains binding sites for the glioma‐associated oncogene (Gli) proteins. We investigated regulation of ANO1 transcription by Gli. ANO1 promoter activity was determined using a luciferase reporter system. Binding and functional effects of Glis on ANO1 transcription and expression were demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 68 publications
(140 reference statements)
0
10
0
Order By: Relevance
“…Here, we show that GLI1FL, but not GLI1ΔN, is capable of acting as a transcriptional repressor of HPV18 early promoters. While GLI1 is generally thought to act only as a transcriptional activator, several groups have also suggested that it might repress certain genes in a context dependent manner [30][31]. Although such overexpression experiments are often difficult to interpret, we believe that the significant difference between the repressor activities of GLI1FL and GLI1ΔN indicates that the effect is direct and not an experimental artefact.…”
Section: Discussionmentioning
confidence: 76%
“…Here, we show that GLI1FL, but not GLI1ΔN, is capable of acting as a transcriptional repressor of HPV18 early promoters. While GLI1 is generally thought to act only as a transcriptional activator, several groups have also suggested that it might repress certain genes in a context dependent manner [30][31]. Although such overexpression experiments are often difficult to interpret, we believe that the significant difference between the repressor activities of GLI1FL and GLI1ΔN indicates that the effect is direct and not an experimental artefact.…”
Section: Discussionmentioning
confidence: 76%
“…In gastric cancer cells, the specificity protein 1 (SP1) was shown to bind ANO1 promoter and recruit the mixed lineage leukemia MLL1 protein to promoter region, facilitating histone H3K4 trimethylation, and subsequently promoting ANO1transcription (Zeng et al, 2019). On the other hand, glioma-associated oncogene proteins Gli1/2 were shown to bind and repress ANO1 promoter activation and ANO1 expression in HEK293 model (Mazzone et al, 2019). DNA methylation was also shown to regulate ANO1 expression.…”
Section: Regulation Of Ano1 Expressionmentioning
confidence: 99%
“…Dysfunction of the pacemaker system contributes to functional gastrointestinal disorders, such as irritable bowel syndrome (IBS), chronic constipation, and intestinal pseudo-obstruction ( 9 12 ). The Ca 2+ -activated Cl − -channel Anoctamin-1 (encoded by the ANO1 gene) and the voltage-gated Na + -channel Nav1.5 ( SCN5A gene) represent molecular markers of the interstitial pacemaker cells in human and mice ( 13 15 ), and DNA variants in the corresponding genes have been shown to associate with increased risk of IBS ( 16 18 ). Ion channel dysfunction (channelopathy) appears to be a plausible pathogenetic mechanism in functional gastrointestinal disorders ( 19 ), as the transient receptor potential cation channel TRPM8 (known as the cold and menthol receptor) and other ion channels have also been implicated in IBS susceptibility and gut dysmotility ( 20 23 ).…”
mentioning
confidence: 99%